Methodology and development tools of the Atlante Multimediale dei Dialetti Veneti (Atti del Sodalizio Glottologico Milanese, 2014)
The paper presents the methodology and development tools used in the Multimedia Atlas of Veneto Dialects (AMDV), a linguistic talking atlas, realized by a team of researchers in dialectology, etymology, phonetics and ethnography. The AMDV is mainly focused on the diachronic comparison of the lexical maps of the Sprach- und Sachatlas Italiens und der Südschweiz (Linguistic and Ethnographic Atlas of Italy and Southern Switzerland) (AIS) by the Swiss linguists Karl Jaberg and Jakob Jud, with the records collected in the same localities at the present time. The project got inspiration from the current linguistic and speech processing methodologies, to give back the dialectal phonic substance behind the more or less questionable transcriptions [Goebl 1994], and to integrate all the relevant ethnographic and etymological documents necessary to understand the Veneto complex linguistic reality. KEYWORDS: Italian dialects, Veneto, linguistic atlas, language documentation, digital humanities